Impact of serving method on the consumption of nutritional supplement drinks: randomized trial in older adults with cognitive impairment. (19th November 2013) - Allen, Victoria J.; Methven, Lisa; Gosney, Margot
Abstract Aim To analyse the influence of serving method on compliance and consumption of nutritional supplement drinks in older adults with cognitive impairment. Background Oral nutritional supplement drinks have positive benefits on increasing nutritional status in undernourished older people leading to weight gain. However, consumption of these drinks is low and therefore limits their effectiveness. Design This study was a non‐blind randomized control trial where participants either consumed nutritional supplement drinks in a glass/beaker or consumed them through a straw inserted directly into the container. Method Participants with long‐standing cognitive impairment were recruited from nursing homes (n = 31) and hospitals (n = 14). Participants were randomized to serving method. Nursing and care staff were instructed to give the supplement drinks three times per day on alternate days over a week by the allocated serving method. The researcher weighed the amount of supplement drink remaining after consumption. Data were collected over 12 months in 2011–2012. Results Forty‐five people participated in this study, mean age 86·7 (sd 7·5) years. After randomization, there was no significant difference between the baseline characteristics of the two groups. Participants randomized to consume nutritional drinks from a glass/beaker drank statistically significantly more than those who consumed them via a straw inserted directly into the container. However, supplements allocated to be given in a glass/beaker were more frequently omitted. Conclusion Nutritional supplement drinks should be given to people with dementia who are able to feed themselves in a glass or a beaker if staffing resources allow (NIHR CSP ref 31101).